Selenium and Prostate Cancer: Analysis of Individual Participant Data From Fifteen Prospective Studies - Allen, Naomi E.; Travis, Ruth C.; Appleby, Paul N.; Albanes, Demetrius; Barnett, Matt J.; Black, Amanda; Bueno-de-Mesquita, H. Bas; Deschasaux, Mélanie; Galan, Pilar; Goodman, Gary E.; Goodman, Phyllis J.; Gunter, Marc J.; et al. (JNCI : Journal of the National Cancer Institute, 2016)
Some observational studies suggest that a higher selenium status is associated with a lower risk of prostate cancer but have been generally too small to provide precise estimates of associations, particularly by disease stage and grade. Collaborating investigators from 15 prospective studies provided individual-participant records (from predominantly men of white European ancestry) on blood or toenail selenium concentrations and prostate cancer risk. Odds ratios of prostate cancer by selenium concentration were estimated using multivariable-adjusted conditional logistic regression. All statistical tests were two-sided. Blood selenium was not associated with the risk of total prostate cancer (multivariable-adjusted odds ratio [OR] per 80 percentile increase = 1.01, 95% confidence interval [CI] = 0.83 to 1.23, based on 4527 case patients and 6021 control subjects). However, there was heterogeneity by disease aggressiveness (ie, advanced stage and/or prostate cancer death, Pheterogeneity = .01), with high blood selenium associated with a lower risk of aggressive disease (OR = 0.43, 95% CI = 0.21 to 0.87) but not with nonaggressive disease. Nail selenium was inversely associated with total prostate cancer (OR = 0.29, 95% CI = 0.22 to 0.40, Ptrend < .001, based on 1970 case patients and 2086 control subjects), including both nonaggressive (OR = 0.33, 95% CI = 0.22 to 0.50) and aggressive disease (OR = 0.18, 95% CI = 0.11 to 0.31, Pheterogeneity = .08). Nail, but not blood, selenium concentration is inversely associated with risk of total prostate cancer, possibly because nails are a more reliable marker of long-term selenium exposure. Both blood and nail selenium concentrations are associated with a reduced risk of aggressive disease, which warrants further investigation.